The Effect of ELSA Speak Application on Students’ Vowels Pronunciation Ability at SMK PGRI 1 Giri Banyuwangi - Nurul Eka Musnianti; Fitria Putri Fernanda; Retno Wulandari; Nadiyatul Hanina; Wulan Wangi (MAN Insan Cendekia Jambi, 2025)
English pronunciation is an important part of language teaching and learning as it affects the communicative competence and efficiency of the learner. One of the most important things in learning English is learning good and correct pronunciation. One of mobile application like ELSA Speak is designed to help students speak English easily, fluently, and confidently. The program features are designed to help students pronounce words such as vowels, consonants, diphthongs, and word stress correctly. The researchers conducted this research to find out whether there is effect or not of ELSA Speak application on students’ vowel pronunciation ability of the X MPLB 1 at SMK PGRI 1 Giri Banyuwangi in the 2023/2024 academic year. There were 28 students as the respondents and this research used pre-experimental quantitative method. The pronunciation test was consisted of 24 words and there were 12 vowels used in this research. The research result showed that the mean scores obtained were 28.79 in pre-test, and 42.71 in post-test. The result of t-test is higher than t-table (26.067 > 2.052). It can be concluded that there is effect of ELSA Speak application on students' vowel pronunciation proficiency at SMK PGRI 1 Giri Banyuwangi in the academic year 2023/2024.